Energy efficiency and implementation of measures to reduce CO2 emission at production facilities in Vietnam - Jakub Dec (Hochschule für angewandte Wissenschaften Hamburg, 2014)
The thesis describes the necessity for energy efficiency with focus on production fa-cilities in developing countries. Starting with present situation on the worldwide energy market, the thesis describes the consequences of rising energy demand and in con-sequence rising CO2 emission. Also policies for energy efficiency and ideas for retro-fitting machines and equipment for energy efficient use are being explained. Especially for a production facility in Vietnam barriers and concrete measures are being analyzed.